Computational thinking for problem solving and managerial mindset training - Dall'Acqua, Luisa, 1962- (Advances in business strategy and competitive advantage., 2021)
"This book expores computational thinking (CT) which involves a set of skills related to the foundations of computer science as a scientific discipline that can be applied to our increasingly digital society, where software technological tools permeate daily life and, consequently, change the management of reality, and mastering of trasversal skills crucial to have success"--